Optical dating of eolian deposits since the last interglacial along the northern margin of the Chinese Loess Plateau. (15th April 2018) - Lü, Tongyan; Sun, Jimin; Gong, Zhijun
Graphical abstract: Highlights: A new OSL chronology of the Shimao section in the northern margin of the Chinese Loess Plateau was established. Both the SAR protocol and the MET-pIRIR protocol were chosen for De determination and age dating. The quartz and K-feldspar ages were cross-checked in the Shimao section. Abstract: Understanding the chronology of eolian sand-loess-paleosol sequences along the northern margin of the Chinese Loess Plateau (CLP) is crucial for comprehending climate change and the advance and retreat of the adjacent Mu Us desert. In this study, a sand-loess-soil sequence from the northern margin of the CLP was studied by applying the single aliquot regenerative (SAR) protocol to quartz grains, and the multi-elevated-temperature post-IR IRSL (MET-pIRIR) protocol to K-feldspar grains. For equivalent dose ( De ) determination, 63–90 μm quartz and K-feldspar grains were used. Our results indicate that the MET-pIRIR ages of K-feldspar grains in this sequence range from 94.4 ± 7.0 ka to 148.3 ± 13.3 ka for the last interglacial paleosol (S1); for the upper part of the section, quartz-based SAR-OSL dating was used, yielding ages spanning from 5.8 ± 0.4 ka to 35.9 ± 4.1 ka. After cross-checking these results with previously-reported isochron OSL and TL ages, the reliability of the MET-pIRIR protocol when applied to the last interglacial paleosol was confirmed. Based on a new OSL chronology of the Shimao profile, the studied eolian deposits can be broadly correlated with the last glacial-interglacial cycle, but their dating also points to sedimentary hiatuses occurring at 94.4 ka, 35.9 ka and 5.8 ka, due most probably to strong wind erosion caused by intensified cold-dry winter monsoonal circulations during the last glacial maxima.